Eosinophilic Colitis and Clostridioides difficile Sepsis With Rapid Remission After Antimicrobial Treatment; A Rare Coincidence and Its Pathogenic Implications - Iacob, Simona Alexandra; Olariu, Mihaela Cristina; Iacob, Diana Gabriela (Frontiers in Medicine, 2020)
Eosinophilic colitis is a rare inflammatory disorder of the digestive tract with chronic evolution and unknown pathophysiological mechanisms. The article describes the case of a 64-year old woman with a history of asthma and hypereosinophilia, who presented to a surgical department for persistent abdominal pain in the past 4 months, weight loss and malabsorption. She was diagnosed with eosinophilic colitis based on the colonoscopic result indicating extensive eosinophilic infiltration of the colonic mucosa correlated with the laboratory data and abdominal CT scan results. Following the colonoscopy, the patient developed fever, hypotension and diarrhea and was transferred to an Infectious Diseases Department with a presumptive diagnosis of abdominal sepsis. Treatment with ertapenem was immediately started. Metronidazole was also added due to a PCR positive stool test for Clostridioides difficile toxins. The patient displayed a rapid remission of the fever and of the intestinal complaints following antibiotic therapy and was discharged after 14 days. During a 3 months follow-up, the patient remained asymptomatic with normal values of laboratory parameters except for a persistent hypereosinophilia. The case outlines two distinguishing features: a histopathologic diagnosis of eosinophilic colitis, a rare differential diagnosis of a patient with chronic abdominal pain and an unexpected and rapid remission of the eosinophilic colitis following the antibiotic treatment and the restoration of the intestinal eubiosis.